Hybrid Soft Soil Tire Model (HSSTM). Part II: Tire-terrain interaction. (December 2019) - Sandu, C.; Taheri, Sh.; Taheri, S.; Gorsich, D.
Highlights: The paper focuses on the interaction of the HSSTM with terrain. Terrain models and tire-terrain contact analyses are presented. Interaction models are presented for tire-deformable terrain and tire-rigid surface. Validation results are presented on rigid and soft terrain vs. experimental data. Abstract: This is the second of three papers on the HSSTM. Part I introduced the tire structure model. Part III presents the tire model parameterization and validation. Part II describes the computational contact models for evaluating the tire/terrain interaction. Its main objective is to characterize the terrain in the normal and tangential directions during tire-terrain interaction. A contact search algorithm examines tire nodal points close to the ground and detects the penetration of the contact surfaces. Next, the contact interface algorithm applies the contact constraints to minimize or eliminate penetration. For deformable terrain, the algorithms are based on semi-empirical formulations and are implemented using a numerical approach in a 3D scheme. The normal and shear stress distribution simulation results for rigid wheel-soil contact are validated against experimental data. The contact interface algorithm for non-deformable terrains is implemented using a distributed 3D brush model enhanced with a transient module for dynamic manoeuvres.